Prevalence of Urinary Incontinence and Health Seeking Behaviours among Middle Age Women - Shrestha, Kalpana; Niraula, Hira; Silwal, Ajita (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Urinary incontinence is one of the most common problems of middle-age. It is oneof the inconvenient experiences that have adverse physical, psychological and social effects. Theshame, taboos and associated knowledge deficit have interfered with its health seeking approachesthat further lower the quality of life. This study was designed to assess the prevalence and healthseeking behaviour on urinary incontinence among middle aged women.Methods: The community-based descriptive cross sectional study was conducted to find out theprevalence and health seeking behaviours on urinary incontinence among middle aged women. Atotal number of 175 women of age group 40-60 years were purposively selected from theKathmandu metropolitan city ward number 31 from among the voters. Face to face interview wasconducted using structured interview schedule. Data were analysed using descriptive (frequency,percentage, mean, standard deviation range) statistics.Results: The study showed that 56% of the women had urinary incontinence. Among them59.18% had stress urinary incontinence, and 40.82% women had both stress and urge urinaryincontinence. Among them, 74.5 % women did not seek medical consultation. Some of thecommon reasons for not seeking medical advices were perceiving urinary incontinence as a naturalprocess (79.22%), lack of knowledge(55.84%) and embarrassment (33.77%). The study findingsalso showed that urinary incontinence was statistically significant with the age of women, parity,place of delivery and mode of delivery.Conclusions: Urinary incontinence is prevalent in more than half of the women and stress urinaryincontinence was common among them. Most of the women had not sought any medical advice.embarrassment, lack of knowledge and perceiving condition as natural were some of the reasonsfor not approaching for medical consultation.